The Role of The Criminal Investigation Unit (Satreskrim) of The Deli Serdang Police Region in Identifying Victims of Criminal Acts - Winata, Edi; Razak Nasution, H. Abdul (PT. Multidisciplinary Press Indonesia, 2024)
The rapid development of various aspects of social, political, economic, security, and cultural life has led to an increase in the quantity and quality of criminal acts, which significantly disrupts society. Criminal acts are unlawful acts committed either intentionally or unintentionally by an individual who can be held accountable for their actions and which are punishable by law. The primary objective of formal criminal law is to seek material truth, and the process of investigation is essential in this regard. The Indonesian National Police, under Law Number 2 of 2002, play a crucial role in conducting investigations using Scientific Crime Investigation (SCI) methods, which integrate science and technology in forensic functions. Scientific Crime Investigation involves gathering and processing evidence with scientific methods, making it one of the most reliable tools in criminal investigations. The role of police identification units in processing crime scenes (TKP) is vital, as even the smallest evidence can be crucial for solving crimes. This research examines the role of the Criminal Investigation Unit (Satreskrim) of the Deli Serdang Police in identifying victims of criminal acts. The findings highlight the importance of forensic evidence in criminal investigations and the crucial role of police units in uncovering the truth.